Middle Eastern Societies in the 20th Century. - Zdanowski, Jerzy (Cambridge Scholars Publishing, 2014)
This book provides a comprehensive overview of the last 100 years in the Middle East from the perspective of social history. It is apt to date the beginning of the modern Middle East to the industrialization era, while it extends its reach into the present. Taking its lead from modernization theory, this book illustrates past expectations of the present and helps to understand everyday occurrences rather than sensational events. It adopts a multi-disciplinary perspective and concentrates on t ...